2006
DOI: 10.1007/s10531-005-6230-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of moose Alces alces L. in boreal forest – the effect on ground beetles (Coleoptera, Carabidae) abundance and diversity

Abstract: The indirect effect of moose Alces alces browsing on ground beetle's abundance and diversity was investigated by pitfall trapping in a mixed coniferous forest in Vestfold County (59°19¢ N, 9°50¢ E, Norway), during the summer of 2002. Three areas with different browsing pressures, ranging from non-to medium-and heavily browsed were chosen and dry weight of bilberry Vaccinium myrtillus and humidity at ground level were measured in the three locations. As predicted, the gradient analyses showed that browsing by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…As many carabid beetles are flightless and prefer more stable habitats [42][43][44], they would provide a good reflection of differences in microenvironments. The results of our study and of a study conducted in western Japan [31] suggest that deer grazing indirectly decreases carabid beetles, in contrast to results obtained in boreal forests [25][26][27][28]. It is noteworthy that more carrion beetles, dung beetles, and camel crickets were collected outside the exclosure than inside (Table 4).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…As many carabid beetles are flightless and prefer more stable habitats [42][43][44], they would provide a good reflection of differences in microenvironments. The results of our study and of a study conducted in western Japan [31] suggest that deer grazing indirectly decreases carabid beetles, in contrast to results obtained in boreal forests [25][26][27][28]. It is noteworthy that more carrion beetles, dung beetles, and camel crickets were collected outside the exclosure than inside (Table 4).…”
Section: Discussioncontrasting
confidence: 81%
“…Studies in boreal forests showed that ungulate grazing can affect carabid beetle populations, but the results are not 2 International Journal of Forestry Research consistent. Some studies reported an increase in carabid beetles as a result of ungulate grazing [25][26][27][28], whereas others reported no effect [29,30]. In Japan, sika deer grazing decreased Sasa nipponica, a dwarf bamboo, but did not affect carabid beetle populations [31].…”
Section: Introductionmentioning
confidence: 99%
“…As carabid beetles utilize the forest floor as a habitat, the decline of understory vegetation because of overbrowsing is likely to result in the alteration of micro-climate conditions of their habitat, such as a decrease in humidity and an increase in light availability, and a higher mortality by predation (Rooney and Waller 2003, Melis et al 2007, Cerda et al 2015). For example, Melis et al (2007) reported that shade tolerant and hygrophilous carabid species were negatively affected by moose browsing as browsing resulted in a decrease of bilberry coverage and changed the humidity and light intensity. Although we did not measure vegetation and other environmental variables, a significant decline in understory cover has been reported at the island site (Takahashi and Kaji 2001; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thiele, 1977Suominen et al, 2003;Melis et al, 2006, 2007Gardner et al, 1997Melis et al, 2007Melis et al, 2006Côté et al, 2004 50 Sasa nipponica Cervus nippon 2003Yokoyama et al, 1996Yokoyama and Shibata, 1998;Itô and Hino, 2005;Furusawa et al, 2005 5 Itô andFurusawa et al, 2005 II. A new closely related species, N. tenuicaulis, was described from Mt.…”
mentioning
confidence: 99%